Tests of income pooling in household decisions - Lechene, V; Attanasio, O (University of Oxford, 2002)
Using the Progresa data from Mexico, we investigate intra-household decision making using a variety of outcomes. We exploit both the experimental nature and the (short) panel dimension of the data to measure the impact of exogenous changes in the intra-household distribution of resources on household decisions. We test for global pooling of resources within households, which would correspond to the unitary model of household decision making. We also exploit a set of questions about power and the decision making process in the household to investigate aspects of strategic interactions between household members. Our findings confirm previous rejections of income pooling. We also cannot reject that the wife's relative income share is a significant determinant of the wife's decision making power in the household, with a higher share of income associated with more decision making power.